2004
DOI: 10.2527/2004.8213_supple40x
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian follicular growth and atresia: The relationship between cell proliferation and survival1,2

Abstract: Growth factors and steroids play an important role in the regulation of ovarian follicular development. In cattle, two of the earliest detectable differences between the healthy dominant follicle selected for development to the ovulatory stage and subordinate follicles destined to undergo atresia are the greater availability of IGF and the greater capacity to produce estradiol in the dominant follicle. We have shown that IGF-I and estradiol stimulate the proliferation of bovine granulosa cells in vitro and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
138
0
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(151 citation statements)
references
References 101 publications
8
138
0
5
Order By: Relevance
“…The moderate increase in total cell protein observed in the presence of FSH could indicate that FSH stimulated proliferation or, alternatively, that FSH prevented apoptosis and increased cell survival. FSH and E 2 are known to act as survival factors to induce granulosa cell proliferation and prevent apoptosis (Gutierrez et al 1997, Yang & Rajamahendran 2000, Jiang et al 2003, Quirk et al 2004. In the present study, TGFB1 caused visible differences in the morphology of granulosa cell clumps, which appeared smaller and more spherical than those in FSH-treated controls.…”
Section: Figurementioning
confidence: 42%
See 1 more Smart Citation
“…The moderate increase in total cell protein observed in the presence of FSH could indicate that FSH stimulated proliferation or, alternatively, that FSH prevented apoptosis and increased cell survival. FSH and E 2 are known to act as survival factors to induce granulosa cell proliferation and prevent apoptosis (Gutierrez et al 1997, Yang & Rajamahendran 2000, Jiang et al 2003, Quirk et al 2004. In the present study, TGFB1 caused visible differences in the morphology of granulosa cell clumps, which appeared smaller and more spherical than those in FSH-treated controls.…”
Section: Figurementioning
confidence: 42%
“…Similarly, TGFB1 alone had no effect on DNA synthesis in cultured bovine granulosa cells (Lerner et al 1995). Therefore, the effects of TGFB1 on granulosa cells could be due to inhibition of the cellsurviving activity of FSH and/or mediated through a loss of E 2 -stimulated cell survival (Yang & Rajamahendran 2000, Quirk et al 2004. Ongoing experiments in our laboratory will test this hypothesis, by investigating the effects of TGFB1 on proliferation and apoptosis of bovine granulosa cells cultured with or without FSH.…”
Section: Figurementioning
confidence: 99%
“…Biological actions of JY-1 on bovine granulosa cells do not mimic the reported effects of the well known oocyte-specific growth factors GDF9 and BMP15 on bovine granulosa cell function (34,35). In vivo, the preovulatory gonadotropin (luteinizing hormone) surge results in decreased estradiol and increased progesterone levels in the follicular fluid of bovine preovulatory follicles (36), and preovulatory granulosa cells exit from the cell cycle and are transformed into nondividing terminally differentiated luteal cells capable of producing high levels of progesterone (37,38). In our culture studies, the increase in progesterone was accompanied by a suppression of the FSH-stimulated increase in granulosa cell numbers and estradiol production, mimicking the in vivo preovulatory follicular environment.…”
Section: Discussionmentioning
confidence: 98%
“…Different kinds of hormone, growth factors, and cytokine are involved in these processes [29][30][31][32]. Bodis J's study found that histamine could directly stimulate the steroid production of ovarial granulosa cells [33].…”
Section: Discussionmentioning
confidence: 99%